THE RELATIONSHIP BETWEEN NURSE CARING BEHAVIOR AND ANXIETY LEVEL OF PATIENTS IN THE INTENSIVE CARE UNIT (ICU) : LITERATURE REVIEW - CAHYATI, YANTI; Sanjaya, Budi; Rosdiana, Ida; Prakasa, Dimas; Triguna, Yudi; Hidayat, Unang Arifin (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIKes Panti Waluya Malang, 2023)
Background: Anxiety often occurs in families who accompany patients during treatment in the ICU. This is because someone treated in the ICU is in a sudden, unplanned state. This causes stressors for patients and their families. Nurse intervention can reduce patient and family stressors by providing good health services and focusing on patient-caring behavior. Purpose: This research can explain the relationship between nurses' caring behavior and the anxiety level of patients and their families in the Intensive Care Unit Method: The method used is a literature review. The procedure for searching and selecting articles was based on Preferred Reporting Items for Systematic Reviews & Meta-Analyses (PRISMA), so four articles were obtained for analysis in the database used in this study, namely Google Scholar, which was limited to publication in the last five years from 2018 to 2023, full-text articles in English. English and Indonesian. Results: The review results of the four articles stated that the analysis of the Univariate and Bivariate statistical tests explained a correlation between respondents' perceptions of nurse caring and the level of anxiety in patients and families with a P value <0.05. Discussion: Nurses providing nursing care are able to provide care with affection, understanding, problem-solving, giving support, giving appreciation, giving attention, and communication which can provide a sense of security and comfort for patients and their families. The existence of sufficient caring behavior from nurses will minimize the incidence of anxiety. Conclusion: There is a relationship between caring behavior and decreased family anxiety in patients treated in the ICU